2011
DOI: 10.1186/1752-1947-5-453
|View full text |Cite
|
Sign up to set email alerts
|

Heterotopic ossification after patellar tendon repair in a man with trisomy 8 mosaicism: a case report and literature review

Abstract: IntroductionHeterotopic ossification is the abnormal formation of lamellar bone in soft tissue. Its presence jeopardizes functional outcome, impairs rehabilitation and increases costs due to subsequent surgical interventions.Case presentationWe present a case of a 32-year-old African-American man with trisomy 8 mosaicism who developed severe heterotopic ossification of his right extensor mechanism subsequent to repair of a patellar tendon rupture.ConclusionTo the best of our knowledge there are no prior report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…A rare and interesting report was described by Chen et al, an extensive heterotopic ossification after patellar tendon repair in a 32-year-old African-American man with a rare trisomy 8 mosaicism. These authors suggested an association between trisomy 8 mosaicism and increased risk of heterotopic ossification [10]. …”
Section: Discussionmentioning
confidence: 99%
“…A rare and interesting report was described by Chen et al, an extensive heterotopic ossification after patellar tendon repair in a 32-year-old African-American man with a rare trisomy 8 mosaicism. These authors suggested an association between trisomy 8 mosaicism and increased risk of heterotopic ossification [10]. …”
Section: Discussionmentioning
confidence: 99%
“…2nd patient - 10 years follow-up, pain free with full ROM. 9 2017, Damrow [ 6 ] 16/male 1 4 × 0.5 cm 2 × 0.5 cm Sleeve fracture of the patella 3-years Surgical excision & patellar tendon reconstruction with semitendinosus tendon autograft & V-Y advancement of the quadriceps tendon 9 months follow-up, asymptomatic 10 1993, Bruijn [ 3 ] 12/female 14/male 2 __ Sleeve fracture of the patella 12-weeks 6-months 1st patient - surgical excision & patellar tendon reconstruction 2nd patient - conservative 1st patient - return to full activity after 6 months 2nd patient - asymptomatic 11 2011, Chen [ 17 ] 32/male b 1 __ Post-operative patellar tendon repair 3-months Knee joint arthrodesis __ 12 2017, Majeed H. [ 13 ] 79/male a 1 3.4 × 2.3 cm 2.9 × 2.2 cm Traumatic patellar tendon injury 49-years Surgical excision & primary repair 6 months follow-up, pain-free with 5 to 100° ROM. 13 2019, Supreeth [ 15 ] 13/male 1 4.5 × 2 × 1 cm 3 × 1.5 × 0.7 cm Traumatic patellar tendon injury 6-weeks Surgical excision & patellar tendon primary repaired with semitendinosus autograft augmentation 6 months follow-up, asymptomatic with full ROM.…”
Section: Discussionmentioning
confidence: 99%
“…If the remaining tendon is not sufficient to support the extensor mechanism after lesion resection, reconstruction with autograft or synthetic graft is recommended [ 6 , 15 , 16 ]. In cases of massive ossification with a risk of re-ossification and a non-functional joint, arthrodesis may be a salvage option [ 17 ]. Many authors recommended NSAID usage after surgical resection as a HO prophylaxis.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported patellar tendon ossification associated with antegrade or retrograde femoral nailing, 1 , 2 spinal cord injury, 3 partial patellectomy, 4 anterior cruciate ligament reconstruction (ACLR) using a bone‐patellar tendon‐bone graft (BPTB), 5 , 6 sleeve fractures of the patella or tibial tuberosity, 7 and genetic disorder. 8 Currently, there is no consensus regarding the standard treatment for patellar tendon ossification, especially when extensive ossification occurs that may require surgical intervention. We herein present a case of severe patellar tendon ossification treated with patellar tendon reconstruction utilizing ipsilateral semitendinosus and gracilis autografts.…”
Section: Introductionmentioning
confidence: 99%